2014
DOI: 10.1016/j.bpj.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features of the Histone Core Structure in Nucleosomes Containing the Histone H2A.B Variant

Abstract: Nucleosomes containing a human histone variant, H2A.B, in an aqueous solution were analyzed by small-angle neutron scattering utilizing a contrast variation technique. Comparisons with the canonical H2A nucleosome structure revealed that the DNA termini of the H2A.B nucleosome are detached from the histone core surface, and flexibly expanded toward the solvent. In contrast, the histone tails are compacted in H2A.B nucleosomes compared to those in canonical H2A nucleosomes, suggesting that they bind to the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Not surprisingly, H2A.B-containing mononucleosomes are unstable [7,8], which is also consistent with numerous studies showing the unwrapping of nucleosomal DNA from the octamer surface at the DNA entry and exit points [810]. This unwrapping of DNA also appears to cause a major reorganization of the histone tails within the nucleosome [11], and allows octamer formation on DNA fragments smaller than the typical 145 base pairs in vitro that are associated with a canonical nucleosome [12]. Third, the N-terminal tails of H2A.B histones distinctively lack lysine residues, but instead are enriched for arginines.…”
Section: Introductionsupporting
confidence: 75%
“…Not surprisingly, H2A.B-containing mononucleosomes are unstable [7,8], which is also consistent with numerous studies showing the unwrapping of nucleosomal DNA from the octamer surface at the DNA entry and exit points [810]. This unwrapping of DNA also appears to cause a major reorganization of the histone tails within the nucleosome [11], and allows octamer formation on DNA fragments smaller than the typical 145 base pairs in vitro that are associated with a canonical nucleosome [12]. Third, the N-terminal tails of H2A.B histones distinctively lack lysine residues, but instead are enriched for arginines.…”
Section: Introductionsupporting
confidence: 75%
“…Nucleosome unwinding experiments using optical tweezers recently revealed the existence of multiple unwound states suggesting the symmetrical split of the octamer through H3-H3 interface under tension at specific conditions [18]. At the same time, equilibrium FRET experiments suggest an open intermediate state of the nucleosome, where the interface between (H3–H4) 2 tetramer and H2A–H2B dimer may be reversibly opened under physiological conditions [19].…”
Section: H2a-h2b Dimer As a Semi-independent Unit In Nucleosome Dynamicsmentioning
confidence: 99%
“…For example, the conformation of H2A.B-variant nucleosome was recently characterized by small angle neutron scattering, which revealed that the DNA ends were detached from the histone core surface and flexibly expanded toward the solvent. At the same time, the histone tails seem to be more compact in this variant compared to tails in canonical nucleosomes [18]. H2A.B-containing nucleosomes are destabilized relative to canonical nucleosomes in a way similar to that seen in hyperacetylated histones [32], and associate with only 118 to 130 bp of DNA [43,44] (Figure 3d).…”
Section: Structure and Stability Of H2a And H2b Variant Nucleosomesmentioning
confidence: 99%
“…Recent X-ray scattering analysis has also supported a more open H2A.B nucleosomal structure, whereby the H2A.B octasome is more extended as compared to the H2A octasome [80•]. In addition, small-angle neutron scattering analysis comparing the H2A.B nucleosome structure with canonical H2A revealed that while the DNA is more loosely attached in the H2A.B nucleosome, the histone tails are more tightly associated with the histone core within the nucleosome [81]. Altogether, these data showed that H2A.B incorporation results in a distinct nucleosome structure whereby the interactions with DNA segments are weaker and, thus, result in a less stable nucleosome.…”
Section: H2ab Localization and Impact On Chromatin Structurementioning
confidence: 98%